Cell-free mitochondrial DNA copy number variation in head and neck squamous cell carcinoma: A study of non-invasive biomarker from Northeast India - Manish Kumar; Shilpee Srivastava; Seram Anil Singh; Anup Kumar Das; Ganesh Chandra Das; Bishal Dhar; Sankar Kumar Ghosh; Rosy Mondal (Tumor Biology)
Head and neck squamous cell carcinoma is the most commonly diagnosed cancer worldwide. The lifestyle, food habits, and customary practices manifest the Northeast Indian population toward higher susceptibility to develop head and neck squamous cell carcinoma. Here, we have investigated the association of smoke and smokeless tobacco, and alcohol with copy number variation of cell-free mitochondrial DNA and cell-free nuclear DNA in cases and controls. Cell-free DNA from plasma was isolated from 50 head and neck squamous cell carcinoma cases and 50 controls with informed written consent using QIAamp Circulating Nucleic Acid Kit. Real-time polymerase chain reaction was done for copy number variation in cell-free mitochondrial DNA and cell-free nuclear DNA. Receiver operating characteristic curve analysis was performed to evaluate the diagnostic application between the two study groups using clinicopathological parameters. The levels of cell-free nuclear DNA and cell-free mitochondrial DNA of cases in association with smoke and smokeless tobacco, alcohol with smoking (p < 0.05) were significantly higher (p < 0.01 and p < 0.001, respectively) than controls. Using receiver operating characteristic curve analysis between head and neck squamous cell carcinoma cases and controls, we distinguished cell-free mitochondrial DNA (cutoff: 19.84 raw Ct; sensitivity: 84%; specificity: 100%; p < 0.001) and cell-free nuclear DNA (cutoff: 463,282 genomic equivalent/mL; sensitivity: 53%; specificity: 87%; p < 0.001). The copy number variation in cases (cell-free nuclear DNA: 5451.66 genomic equivalent/mL and cell-free mitochondrial DNA: 29,103,476.15 genomic equivalent/mL) and controls (cell-free nuclear DNA: 1650.9 genomic equivalent/mL and cell-free mitochondrial DNA: 9,189,312.54 genomic equivalent/mL), respectively. Our result indicates that the cell-free mitochondrial DNA content is highly associated with smoke and smokeless tobacco, betel quid chewing, and alcohol which shows greater promises, holding the key characteristics of diagnostic biomarkers, that is, minimal invasiveness, high specificity, and sensitivity.